Pengaruh Current Ratio, Debt To Equity Ratio dan Net Profit Margin Terhadap Kebijakn Dividen Pada Perusahaan Subsektor Otomotif Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Yanti, Feri; Purba, Yessica Sardina (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to examine and analyze the effect of current ratio, debt to equity ratio and net profit margin on dividend policy in automotive sub-sector companies. The research method used in this study uses quantitative research methods with quantitative descriptive research that is explanatory research. The population of this research is all the automotive sub-sector companies listed on the Indonesia Stock Exchange totaling 13 companies. The sample of this research is 12 companies with purposive sampling technique. The data analysis method used is multiple linear regression. The results of the study state that partially current ratio and debt to equity ratio have a negative and significant effect on dividend policy, while net profit margin has a positive and significant effect on dividend policy. Simultaneous test results state that the current ratio, debt to equity ratio and net profit margin affect dividend policy with a coefficient of determination of 15.7% while the rest is explained by variables that are not examined.